Efektivitas Gamification Aplikasi Duolingo dalam Meningkatkan Penguasaan Simple Past dan Past Perfect Tense (Studi Komparatif) - Muharromah, I Aeni (STKIP PGRI Bandar Lampung, 2025)
Mastering English grammar, specifically the distinction between Simple Past and Past Perfect Tense, often poses a significant challenge for Indonesian students due to linguistic interference from their native language, which lacks a tense system. This study aims to examine the effectiveness of using the gamified application Duolingo compared to conventional learning methods in enhancing students' ability to discriminate between these two tenses. Employing a quasi-experimental design (Nonequivalent Control Group Design), the study involved 46 first-semester English Literature students divided into a control group (n=24) and an experimental group (n=22). Data were collected through pre-test and post-test instruments and analyzed using Normalized Gain (N-Gain) scores and independent sample t-tests. The results indicated that the experimental group using Duolingo achieved a higher mean post-test score (89.09) than the control group (80.42). N-Gain analysis revealed that Duolingo's effectiveness fell into the